The Tripartite Cascade Strategy Amplifies Cellular Oxidative Stress to Disrupt Oxidation–Reduction Homeostasis for Tumor Immunogenic Cell Death - Jiang, Lingdong; Chen, Xiaojia; Gu, Yuqing; Deng, Fuan; Song, Yue; Mao, Chunping; Tong, Yuqi; Wang, Fengyi; Zhang, Wenyuan; Liu, Yujing; Chen, Yichi; Shi, Haonan; et al. (ACS materials letters, 2025)
Immunogenic cell death (ICD) induced by intracellular oxidation–reduction homeostasis imbalance is a classic mechanism in cancer immunotherapy. Herein, we propose a tripartite strategy to amplify cellular oxidative stress based on a combination of peptidic nanoparticles (TPFNO/CCA NPs) of host–guest drug-loading, fibrillar transformation, and NO generation. Cinnamaldehyde (CA) was released from TPFNO/CCA NPs due to Schiff base bond breakage within the lysosome, promoting excessive ROS generation. The residual TPFNO/C NPs bind the mitochondria, where excessive ROS induces the host–guest disintegration of ferrocene/β-cyclodextrin. The β-sheet TPFNO peptide could further transform into a fibrillar network on the mitochondria surface, leading to a further surge of ROS. Concurrently, the TPFNO peptide would locally release NO gas by consuming intracellular glutathione. NO further reacts with ROS and yields ONOO–, exacerbating mitochondrial dysfunction. Through a synergistic cascade of ROS generation and glutathione consumption, TPFNO/CCA NPs efficiently amplify oxidative stress, inducing potent immunogenic death in tumor cells.